The Role of Biliary Drainage in Patients with Pancreatic Adenocarcinoma - Toki, Maria I; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is one of the leading causes of cancer deaths worldwide and constitutes a major public health problem. One of the most common symptoms associated with pancreatic adenocarcinoma is jaundice, caused by the obstruction of common bile duct. Endobiliary stenting is used to relief these patients either preoperatively or merely for palliation and plastic or metal stents are usually endoscopically or percutaneously placed. Two interesting studies were presented at the 2014 ASCO Gastrointestinal Cancers Symposium. Strom et al. sought to investigate the effect of preoperative biliary drainage on recurrence and survival and they concluded that percutaneous biliary decompression was an independent predictor of worse overall survival and was associated with non-significant increase in hepatic recurrence (Abstract #314). Montero et al. presented the results of their study regarding the cost-effectiveness of metal stents in patients with inoperable pancreatic cancer and they concluded that placement of metal biliary stents is cost saving, improves overall survival and quality-adjusted survival compared with plastic stents (Abstract #260). Both studies concluded to useful results that along with the existing literature and formulated guidelines may help the provision of more effective, higher quality management of these patients. Image: Stents